TEKNOLOGI INFORMASI DAN KOMUNIKASI BERUPA E-BOOK BERBASIS KEARIFAN LOKAL DALAM PENGEMBANGAN BAHAN AJAR BAHASA DAN SASTRA INDONESIA - Hainur Anisa (Universitas Negeri Medan, 2019)
Abstract The development of material is the basis for learning and a practical responsibility. As a basis, the material learns principles and procedures in designing, implementing and evaluating language learning materials. Associating with local wisdom will make students better recognize each other's culture. The development of the all-round technology becomes one of the examples of the times that certainly cannot be ignored by anyone. Students who live in the IT era will naturally feel more interested in IT-based learning. This engineering came up with ideas related to the development of teaching materials and the times. Developing teaching materials in the form of digital books today is the right choice for teachers because it will make students more interested. The needs in the world of education are very complex starting from the need for sources of knowledge, namely books, reliable teachers, adequate places, and other supporting needs. E-books are a pretty good alternative because of their digital nature so they don't use paper and only require a set of devices that can read them like cell phones, computers, laptops, and other devices. In the E-book there are several book formats that can be used. This e-book will be in the form of a book which consists of videos, images, text, audio, animation, and evaluation in the form of interesting questions based on local wisdom. Keywords: Teaching Materials, Local Wisdom, Digital, E-Book